2013
DOI: 10.3109/02713683.2013.841259
|View full text |Cite
|
Sign up to set email alerts
|

Pachymetry Map of Corneal Epithelium in Children Wearing Orthokeratology Contact Lenses

Abstract: The epithelial thickness map automatically generated by FD-OCT can provide regional information about corneal epithelium thickness following overnight wearing of OK lenses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 31 publications
7
43
1
Order By: Relevance
“…Thinning of the central corneal epithelium has been demonstrated in both clinical and histological studies of overnight OK lens wear [16,17] ; however, the reported changes in the mid-peripheral corneal epithelium have been less consistent. In a previous study by our research group [5] , we found that the paracentral corneal epithelium thickened most in the inferior quadrant, which is similar to the findings of the present study and supported by the findings of a recent study by Reinstein et al [3] . Lian et al [4] used a custom-made OCT to measure the thickness profile changes of the corneal epithelium after OK lens wear and found that the nasal and temporal mid-peripheral (4-6mm) epithelium thickened after OK wear; however, they found no mid-peripheral epithelial thickening along the vertical meridian.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Thinning of the central corneal epithelium has been demonstrated in both clinical and histological studies of overnight OK lens wear [16,17] ; however, the reported changes in the mid-peripheral corneal epithelium have been less consistent. In a previous study by our research group [5] , we found that the paracentral corneal epithelium thickened most in the inferior quadrant, which is similar to the findings of the present study and supported by the findings of a recent study by Reinstein et al [3] . Lian et al [4] used a custom-made OCT to measure the thickness profile changes of the corneal epithelium after OK lens wear and found that the nasal and temporal mid-peripheral (4-6mm) epithelium thickened after OK wear; however, they found no mid-peripheral epithelial thickening along the vertical meridian.…”
Section: Discussionsupporting
confidence: 93%
“…Corneal powers from SimK were derived from the axial curvature map and were used in the current study. radials, 1024 axial scans each, repeated five times) was used for imaging the cornea [5] . Subjects were asked to focus their vision on a provided fixation target.…”
Section: Corneal Topographymentioning
confidence: 99%
See 1 more Smart Citation
“…9 The data output included total corneal and corneal epithelial thickness maps (representative examples from both groups are shown in Fig. A Fourier-domain OCT setup (RTVue S, Optovue, Inc, California) with a corneal adaptor module was used to measure the central 6-mm corneal epithelial topography.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…The measurement of corneal epithelium thickness provides important information for assessing corneal function, especially in patients who have been exposed to cataract surgery, in contact lens wearers and, for diagnosing diseases like keratoconus or dry eye syndrome. 3-6 With the attachment of the pachometer to the slit-lamp, epithelial thickness dimensions could be a convenient measurement to obtain during routine clinical visits. However, the relative difficulty for visualizing the epithelium, mainly due to the low magnification of the traditional slit-lamp, makes pachymetric measurements of the corneal layers markedly troublesome.…”
Section: Introductionmentioning
confidence: 99%